Hydrogenated blue titania with high solar absorption and greatly improved photocatalysis. Issue 8 (9th February 2016) - Zhu, Guilian; Shan, Yufeng; Lin, Tianquan; Zhao, Wenli; Xu, Jijian; Tian, Zhangliu; Zhang, Hui; Zheng, Chong; Huang, Fuqiang
Abstract : Doped hydrogen atoms, instead of the amorphous shells, are demonstrated to be essential for the significantly enhanced solar absorption and photocatalytic performance of bluish hydrogenated titania, which is synthesized by a TiH2 -assisted method. Abstract : Hydrogenated black titania, with a crystalline core/amorphous shell structure, has attracted global interest due to its excellent photocatalytic properties. However, the understanding of its structure–property relationships remains a great challenge and a more effective method to produce hydrogenated titania is desirable. Herein, we report a TiH2 assisted reduction method to synthesize bluish hydrogenated titania (TiO2− x :H) that is highly crystallized. The characteristic amorphous shells, which are essential for the enhancement of solar absorption and photocatalysis in many reported hydrogenated titania, are completely removed by hydrogen peroxide. The blue TiO2− x :H sample without amorphous shells delivers not only significantly improved visible- and infrared-light absorption but also greatly enhanced photocatalytic activity compared to pristine TiO2 . Its water decontamination is 2.5 times faster and the hydrogen production was 1.9-fold higher over pristine TiO2 . Photoelectrochemical measurement reveals greatly improved carrier density and photocurrent (a 4.3-fold increase) in the reduced TiO2− x :H samples. This work develops a facile and versatile method to prepare hydrogenated titania and proposes a new understanding of the hydrogenated titania that doped hydrogen atoms, instead of the amorphous shells, are essential for its high photocatalytic performance.